Mycobacterial IHF is a highly dynamic nucleoid-associated protein that assists HupB in organizing chromatin - Hołówka, Joanna; Łebkowski, Tomasz; Feddersen, Helge; Giacomelli, Giacomo; Drużka, Karolina; Makowski, Łukasz; Trojanowski, Damian; Broda, Natalia; Bramkamp, Marc; Zakrzewska-Czerwińska, Jolanta (Frontiers in Microbiology, 2023)
Nucleoid-associated proteins (NAPs) crucially contribute to organizing bacterial chromatin and regulating gene expression. Among the most highly expressed NAPs are the HU and IHF proteins, whose functional homologues, HupB and mIHF, are found in mycobacteria. Despite their importance for the pathogenicity and/or survival of tubercle bacilli, the role of these proteins in mycobacterial chromosome organization remains unknown. Here, we used various approaches, including super-resolution microscopy, to perform a comprehensive analysis of the roles of HupB and mIHF in chromosome organization. We report that HupB is a structural agent that maintains chromosome integrity on a local scale, and that the lack of this protein alters chromosome morphology. In contrast, mIHF is a highly dynamic protein that binds DNA only transiently, exhibits susceptibility to the chromosomal DNA topology changes and whose depletion leads to the growth arrest of tubercle bacilli. Additionally, we have shown that depletion of msIHF leads to chromosome shrinkage and replication inhibition.